2017
DOI: 10.4103/0366-6999.196587
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of Lewis Lung Carcinoma Cells Induced by Microwave via p53 and Proapoptotic Proteins In vivo

Abstract: Background:Microwave therapy is a minimal invasive procedure and has been employed in clinical practice for the treatment of various types of cancers. However, its therapeutic application in non-small-cell lung cancer and the underlying mechanism remains to be investigated. This study aimed to investigate its effect on Lewis lung carcinoma (LLC) tumor in vivo.Methods:Fifty LLC tumor-bearing C57BL/6 mice were adopted to assess the effect of microwave radiation on the growth and apoptosis of LLC tumor in vivo. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…As previously described, the tumor tissue in each mouse was dissected, fixed in 10% formaldehyde for 24 h, and embedded in paraffin wax. Sections (2∼3 μm) were stained by terminal deoxynucleotidyl TUNEL using the in situ cell death detection kit (Roche) according to the manufacturer’s instructions to detect the apoptotic cells ( Zhang et al, 2017 ). Apoptotic cells were manifested by green staining in the nuclei under microscopy and five microscopic fields (×400) of each section were randomly examined, and the positive cells were counted by a single-blinded observer in a coded randomized order.…”
Section: Methodsmentioning
confidence: 99%
“…As previously described, the tumor tissue in each mouse was dissected, fixed in 10% formaldehyde for 24 h, and embedded in paraffin wax. Sections (2∼3 μm) were stained by terminal deoxynucleotidyl TUNEL using the in situ cell death detection kit (Roche) according to the manufacturer’s instructions to detect the apoptotic cells ( Zhang et al, 2017 ). Apoptotic cells were manifested by green staining in the nuclei under microscopy and five microscopic fields (×400) of each section were randomly examined, and the positive cells were counted by a single-blinded observer in a coded randomized order.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Zhao et al (12) also showed that microwave dose-dependently induced cellular apoptosis, cell cycle arrest and decreased cytotoxic activity in Natural killer cells 92 (NK-92), possibly through extracellular regulated protein kinases (ERK)-mediated regulation of apoptosis and perforin expression. Additionally, Zhang et al (13) demonstrated that continuous microwave radiation once a day for up to 7 days efficiently induced Lewis lung carcinoma (LLC) tumor cell apoptosis in mice even at the low intensity of 10 mW/cm 2 for 5 min each time, and revealed that non-thermal effect played a critical role in the induction of tumor cell apoptosis in-vivo.…”
Section: Response Of Biological Cells To Microwave Irradiation Effect Of Microwaves On Cellsmentioning
confidence: 99%
“…Changed possibly through ERK-mediated regulation of apoptosis and perforin expression 2017 Zhang et al (13) 10 mW/cm 2 LLC cells cell apoptosis changed 2006 Zhadobov et al (15) 60 GHz Artificial Biological Membranes lateral pressure increased 1995 Geletyuk et al (16) 42.25 GHz kidney cells K+ channel changed 2014 Rougier et al (17) 2.45 GHz Escherichia coli cellular permeability increased 2014 Zeng et al (18) 2.45 GHz Yeast cellular permeability increased…”
Section: Ultrastructural Changes Cellular Apoptosis and Cell Cycle Regulationmentioning
confidence: 99%
“…[ 10 ] Some studies have also claimed that these fields can reduce cell growth and survival and induce apoptosis in cells. [ 11 12 13 14 15 16 ] In contrast, there are other studies that do not confirm the above and their results have shown that electromagnetic waves and fields have no effect on cell growth and survival. [ 6 7 8 ]…”
Section: Introductionmentioning
confidence: 99%